Adipose tissue development during early life: novel insights into energy balance from small and large mammals - Symonds, Michael E.; Pope, Mark; Budge, Helen (Proceedings of the Nutrition Society, 2012)
Since the rediscovery of brown adipose tissue (BAT) in adult human subjects in 2007, there has been a dramatic resurgence in research interest in its role in heat production and energy balance. This has coincided with a reassessment of the origins of BAT and the suggestion that brown preadipocytes could share a common lineage with skeletal myoblasts. In precocial newborns, such as sheep, the onset of non-shivering thermogenesis through activation of the BAT-specific uncoupling protein 1 (UCP1) is essential for effective adaptation to the cold exposure of the extra-uterine environment. This is mediated by a combination of endocrine adaptations which accompany normal parturition at birth and further endocrine stimulation from the mother's milk. Three distinct adipose depots have been identified in all species studied to date. These contain either primarily white, primarily brown or a mix of brown and white adipocytes. The latter tissue type is present, at least, in the fetus and, thereafter, appears to take on the characteristics of white adipose tissue during postnatal development. It is becoming apparent that a range of organ-specific mechanisms can promote UCP1 expression. They include the liver, heart and skeletal muscle, and involve unique endocrine systems that are stimulated by cold exposure and/or exercise. These multiple pathways that promote BAT function vary with age and between species that may determine the potential to be manipulated in early life. Such interventions could modify, or reverse, the normal ontogenic pathway by which BAT disappears after birth, thereby facilitating BAT thermogenesis through the life cycle.